Analisis Sistem Informasi Manajemen Kepegawaian dalam Rangka Mewujudkan Data Informasi yang Mutakhir, Terintegrasi pada BKPSDM Kabupaten Sumba Barat - Umbu Sius Rina Weikalowo; Adelbertus Umbu Janga; Diana Reby Sabawaly (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2026)
This study aims to analyze the application of personnel management information systems at the West Sumba Regency Personnel and Human Resources Development Agency (BKPSDM). The main focus of the research is to assess how an integrated information system is able to produce up-to-date, accurate, and can support the decision-making process in personnel policy. An integrated information system is expected to facilitate employee data management, improve administrative efficiency, and strengthen transparency in human resource management. The research method uses a qualitative approach with case studies, through interviews with relevant officials, direct observation, and analysis of relevant documents. The results of the study show that the implementation of an integrated personnel management information system has a positive impact in the form of accelerating administrative processes, reducing data input errors, and facilitating access to information for interested parties. However, the research also found a number of challenges, such as the limitation of human resources trained in the use of technology systems and infrastructure that is not yet optimal. This study concludes that strengthening human resource capacity and increasing infrastructure support is a strategic step to optimize the personnel management information system. The research recommendations are expected to be a reference for the West Sumba Regency BKPSDM and other government agencies in developing a more effective and sustainable information system.